Γ‐Glutamylcysteine‐ and Cysteinylglycine‐Directed Growth of Chiral Gold Nanoparticles and their Crystallographic Analysis. Issue 31 (25th May 2020) - Kim, Hyeohn; Im, Sang Won; Cho, Nam Heon; Seo, Da Hye; Kim, Ryeong Myeong; Lim, Yae‐Chan; Lee, Hye‐Eun; Ahn, Hyo‐Yong; Nam, Ki Tae
Abstract: Chiral optical metamaterials with delicate structures are in high demand in various fields because of their strong light–matter interactions. Recently, a scalable strategy for the synthesis of chiral plasmonic nanoparticles (NPs) using amino acids and peptides has been reported. Reported herein, 3D chiral gold NPs were synthesized using dipeptide γ‐Glu‐Cys and Cys‐Gly and analyzed crystallographically. The γ‐Glu‐Cys‐directed NPs present a cube‐like outline with a protruding chiral wing. In comparison, the NPs synthesized with Cys‐Gly exhibited a rhombic dodecahedron‐like outline with curved edges and elliptical cavities on each face. Morphology analysis of intermediates indicated that γ‐Glu‐Cys generated an intermediate concave hexoctahedron morphology, while Cys‐Gly formed a concave rhombic dodecahedron. NPs synthesized with Cys‐Gly are named 432 helicoid V because of their unique morphology and growth pathway. Abstract : 3D chiral gold NPs were synthesized using dipeptide γ‐glutamylcysteine (γ‐Glu‐Cys) and cysteinylglycine (Cys‐Gly) structure‐directing agents. Crystallographic analysis of the γ‐Glu‐Cys‐directed NPs revealed a cube‐like outline with a protruding chiral wing, whereas NPs synthesized with Cys‐Gly—so‐called 432 helicoid V—exhibit a rhombic dodecahedron‐like outline with curved edges and elliptical cavities on each face.